Pengaruh Konsentrasi Belajar, Efikasi Diri dan Metode Pembelajaran terhadap Pemahaman Materi Ma As-Sa’adah Lampah Kedamean Gresik - Yulianto Yulianto; Eli Masnawati; Didit Darmawan (Departement of Mathematics Education, 2024)
A number of students had difficulty understanding the lesson material. The causes can vary, ranging from lack of focus (low concentration), failure in self-confidence (low self-efficacy), to a mismatch in the learning methods used. This research aims to investigate how learning concentration, self-efficacy, and learning methods interact with each other and contribute to students' understanding of the material at MA As-Sa'adah Lampah Kedamean Gresik. This research uses a quantitative approach which will be used in this research to measure the influence of variables such as learning concentration, self-efficacy, and learning methods on students' understanding of the material. From the research it can be concluded that this third factor has a significant role in determining students' level of understanding. High learning concentration allows students to focus fully on learning material, acquire information more effectively, and encourage deeper understanding. This emphasizes the need to create a learning environment that is conducive to improving student concentration, including reducing distractions and providing necessary support.